Diversity and taxonomic revision of methanogens and other archaea in the intestinal tract of terrestrial arthropods - Evgenii Protasov; James O. Nonoh; Joana M. Kästle Silva; Undine S. Mies; Vincent Hervé; Carsten Dietrich; Kristina Lang; Lena Mikulski; Katja Platt; Anja Poehlein; Tim Köhler-Ramm; Edouard Miambi; et al. (Frontiers in Microbiology, 2023)
Methane emission by terrestrial invertebrates is restricted to millipedes, termites, cockroaches, and scarab beetles. The arthropod-associated archaea known to date belong to the orders Methanobacteriales, Methanomassiliicoccales, Methanomicrobiales, and Methanosarcinales, and in a few cases also to non-methanogenic Nitrososphaerales and Bathyarchaeales. However, all major host groups are severely undersampled, and the taxonomy of existing lineages is not well developed. Full-length 16S rRNA gene sequences and genomes of arthropod-associated archaea are scarce, reference databases lack resolution, and the names of many taxa are either not validly published or under-classified and require revision. Here, we investigated the diversity of archaea in a wide range of methane-emitting arthropods, combining phylogenomic analysis of isolates and metagenome-assembled genomes (MAGs) with amplicon sequencing of full-length 16S rRNA genes. Our results allowed us to describe numerous new species in hitherto undescribed taxa among the orders Methanobacteriales (Methanacia, Methanarmilla, Methanobaculum, Methanobinarius, Methanocatella, Methanoflexus, Methanorudis, and Methanovirga, all gen. nova), Methanomicrobiales (Methanofilum and Methanorbis, both gen. nova), Methanosarcinales (Methanofrustulum and Methanolapillus, both gen. nova), Methanomassiliicoccales (Methanomethylophilaceae fam. nov., Methanarcanum, Methanogranum, Methanomethylophilus, Methanomicula, Methanoplasma, Methanoprimaticola, all gen. nova), and the new family Bathycorpusculaceae (Bathycorpusculum gen. nov.). Reclassification of amplicon libraries from this and previous studies using this new taxonomic framework revealed that arthropods harbor only CO2 and methyl-reducing hydrogenotrophic methanogens. Numerous genus-level lineages appear to be present exclusively in arthropods, suggesting long evolutionary trajectories with their termite, cockroach, and millipede hosts, and a radiation into various microhabitats and ecological niches provided by their digestive tracts (e.g., hindgut compartments, gut wall, or anaerobic protists). The distribution patterns among the different host groups are often complex, indicating a mixed mode of transmission and a parallel evolution of invertebrate and vertebrate-associated lineages.